2018
DOI: 10.1007/s00441-018-2883-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of maternal circuits by oxytocin

Abstract: Motherhood in mammals involves tremendous changes throughout the body and central nervous system, which support attention and nurturing of infants. Maternal care consists of complex behaviors, such as nursing and protection of the offspring, requiring new mothers to become highly sensitive to infant needs. Long-lasting neural plasticity in various regions of the cerebral cortex may enable the perception and recognition of infant cues, important for appropriate caregiving responses. Recent findings have demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 145 publications
(276 reference statements)
0
37
0
Order By: Relevance
“…The expression levels of estrogen receptors and oxytocin receptors in the MPOA and other regions such as the amygdala, are positively correlated with natural variations in maternal care (Champagne et al, 2001). It is well known that exposures to estrogens significantly increase oxytocin receptor expression in various brain regions directly involved in maternal behavior (Bale et al, 1995;Pedersen, 1997) but cortical regions are also impacted; oxytocin activity via oxytocin receptor expressing neurons in the auditory cortex and in the somatosensory cortex of mouse dams increases the salience of pup calls, facilitating pup retrieval (Sabihi et al, 2014;Marlin et al, 2015;Valtcheva & Froemke, 2018). While the OXT system is mostly activated by the social interaction with the pups, the onset of activation and fine tuning with early offspring-mother communication is modulated by steroid release during pregnancy.…”
Section: Neurobiological Consequences Of Hormonal Changesmentioning
confidence: 99%
“…The expression levels of estrogen receptors and oxytocin receptors in the MPOA and other regions such as the amygdala, are positively correlated with natural variations in maternal care (Champagne et al, 2001). It is well known that exposures to estrogens significantly increase oxytocin receptor expression in various brain regions directly involved in maternal behavior (Bale et al, 1995;Pedersen, 1997) but cortical regions are also impacted; oxytocin activity via oxytocin receptor expressing neurons in the auditory cortex and in the somatosensory cortex of mouse dams increases the salience of pup calls, facilitating pup retrieval (Sabihi et al, 2014;Marlin et al, 2015;Valtcheva & Froemke, 2018). While the OXT system is mostly activated by the social interaction with the pups, the onset of activation and fine tuning with early offspring-mother communication is modulated by steroid release during pregnancy.…”
Section: Neurobiological Consequences Of Hormonal Changesmentioning
confidence: 99%
“…In addition, future studies are needed to determine whether the role of PV-related inhibition on auditory discrimination abilities is lateralized. Whereas previous studies have reported impaired performance in sound localization (Heffner and Heffner, 1990) and discrimination of frequency-modulated tones (Rybalko et al, 2006) following lesions in either left, right, or bilateral auditory cortex, more recent investigations suggest that the processing of physiologically-relevant stimuli might indeed be lateralized (Valtcheva and Froemke, 2019). Given that evidence to date regarding the lateralization of auditory discrimination abilities remains inconclusive, and the more general focus of the present investigation, we decided to perform bilateral virus injections.…”
Section: Discussionmentioning
confidence: 98%
“…There was also a nonsignificant trend for IN OXT to improve the correlation between mother and pup USVs. If the removal from the home cage at the start of the test disrupted the coordination between mothers and pups, IN OXT may be mediating this negative effect by increasing the salience of pup whine stimuli (Valtcheva & Froemke, 2019), allowing mothers to more effectively and efficiently cope with the challenge. During reunion, we found support for our initial prediction: maternal simple sweeps and pup whines positively correlated.…”
Section: Fig 4 Correlations Between Maternal Simple Sweep Usvs Andmentioning
confidence: 99%